Effect of Pozzolanic Cement Exposure in Nile Tilapia (Oreochromis niloticus) - Şevki Kayış; Mert Minaz; Akif Er (Aquatic Sciences and Engineering)
Cement used in structures such as bridges, dams, and retaining walls built on the aquatic ecosystem harms different organisms. The current study reveals the effect of pozzolanic cement (PC) on Nile Tilapia (Oreochromis niloticus). The LC50 value for O. niloticus exposed to 6 different PC concentrations for 24 hours was calculated as 306.66 mg L-1. Increasing PC concentration significantly increased the pH of water (<10) at the end of the study (p<0.05). The increase in pH level showed a positive correlation with the increase in fish mortality (p<0.05). In addition, PC negatively affected the hematological parameters of fish. Thus, the current study reveals the negative effects of PC on O. niloticus in the acute period. Future studies should focus on developing cement with environmentally friendly materials that will not affect the pH level of water.